Short Communication: Determination of the age of the Paddy Field Frog, Fejervarya cancrivora (Anura: Dicroglossidae) by using skeletochronology - Ni Luh Putu Rischa Phadmacanty; Hellen Kurniati (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Phadmacanty NLPR, Kurniati H. 2019. Short Communication: Determination of the age of the Paddy Field Frog, Fejervarya cancrivora (Anura: Dicroglossidae) by using skeletochronology. Biodiversitas 20: 2739-2743. The age of 102 individuals of paddy field frog (Fejervarya cancrivora) from Karawang District, West Java, Indonesia was skeletochronological determined. Hematoxylinophilic lines interpreted as lines of arrested growth (LAG) were observed clearly in the femur bone suggesting that this technique can be used to estimate the age of the frog, although the level of accuracy is likely to be strongly influenced by external and internal factor. In general, age estimates look close to accuracy at mature age levels; which one LAG equals the age of the frog that has passed one year old. The age structure of F. cancrivora from a paddy field in Karawang District has the maximum age of five years in females and four years in males. In general, adult females were not significantly larger than adult males.